Raising the bar. Review of Cycling Safety Policies in the European Union. - Steriu, Mircea (My University, 2012)
For more information see: www.etsc.eu/
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Verkehrspolitik; Verkehrsverhalten; Radverkehrssicherheit; Handlungsempfehlung